Taking Innovations to Scale: Methods, Applications and Lessons - Cooley, Larry; Linn, Johannes F. (R4D, 2014)
The international development community increasingly recognizes the ne ed to go beyond fragmented, one-of projects. In response, there is now much talk and some action on scaling up successful innovations and pi lot projects with an explicit goal of achieving sustainable impact at scale. However, many questions remain about the practical implications of pursuing a systematic scaling up approach and about how the approa ches being pursued by diferent institutions and practitioners relate t o each other.